Women of the dunes [large type] - Maine, Sarah (Center Point Large Print, 2018)
"An intriguing mystery set on the coast of Western Scotland in which the lives of a ninth-century Norsewoman, a nineteenth-century woman, and a twenty-first-century archeologist weave together after a body is discovered in the dunes"--